Endogenous activated protein C limits cancer cell extravasation through sphingosine-1-phosphate receptor 1–mediated vascular endothelial barrier enhancement - Van Sluis, Geerte L. (American Society of Hematology, 2009)
Activated protein C (APC) has both anticoagulant activity and direct cell-signaling properties. APC has been reported to promote cancer cell migration/invasion and to inhibit apoptosis and therefore may exacerbate metastasis. Opposing these activities, APC signaling protects the vascular endothelial barrier through sphingosine-1-phosphate receptor-1 (S(1)P(1))activation, which may counteract cancer cell extravasation. Here, we provide evidence that endogenous APC limits cancer cell extravasation, with in vivo use of monoclonal antibodies against APC. The protective effect of endogenous APC depends on its signaling properties. The MAPC1591 antibody that only blocks anticoagulant activity of APC does not affect cancer cell extravasation as opposed to MPC1609 that blocks anticoagulant and signaling properties of APC. Combined administration of anti-APC antibodies and S(1)P(1) agonist (SEW2871) resulted in a similar number of pulmonary foci in mice in presence and absence of APC, indicating that the protective effect of APC depends on the S(1)P(1) pathway. Moreover, endogenous APC prevents cancer cell–induced vascular leakage as assessed by the Evans Blue Dye assay, and SEW2871 treatment reversed MPC1609-dependent vascular leakage. Finally, we show that cancer cells combined with MPC1609 treatment diminished endothelial VE-cadherin expression. In conclusion, endogenous APC limits cancer cell extravasation because of S(1)P(1)-mediated VE-cadherin–dependent vascular barrier enhancement.